2005
DOI: 10.1080/13625180500034911
|View full text |Cite
|
Sign up to set email alerts
|

Modern and traditional practices of Turkish infertile couples

Abstract: It was concluded that traditional practices were more prevalent in the rural areas and among the older couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 7 publications
1
39
1
5
Order By: Relevance
“…Traditional medicine strategies included consulting the neighborhood midwife or hodja 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 about using herbal mixtures. Such methods resembled the strategies found in other studies in Turkey [21,29,32]. Although strategies peculiar to our culture may be a part of seeking spiritual assistance or keeping expectations alive, these approaches were not as effective as other coping methods for the women in the present study.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Traditional medicine strategies included consulting the neighborhood midwife or hodja 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 about using herbal mixtures. Such methods resembled the strategies found in other studies in Turkey [21,29,32]. Although strategies peculiar to our culture may be a part of seeking spiritual assistance or keeping expectations alive, these approaches were not as effective as other coping methods for the women in the present study.…”
Section: Discussionsupporting
confidence: 61%
“…The participants' reports suggested that having a child was seen as women's primary social duty, which appeared to reflect wider societal attitudes. Women who internalized this role and considered being childless as a violation of social norms often perceived their infertility as a threat to their personal identity [9,12,21,25,27]. Furthermore, although not an obvious physical inadequacy, infertility appeared to engender stigmatization because of the accompanying feelings of embarrassment, wanting to hide, and the pressure to have a child [20].…”
Section: Discussionmentioning
confidence: 99%
“…[6] Especially in traditional societies having a child is the determinative factor of the women's social status, therefore infertile women may feel the social stigma more strongly. [7] Lifestyle related factors as smoking, and alcohol use, insufficient exercise, sexually transmitted diseases, advanced age, caffein consumption, obesity, and stress appear to occupy an important place among risk factors of infertility. [8,9] Interestingly, these behaviours or conditions which adversely affect reproductive potential are modifiable or preventable factors.…”
Section: Introductionmentioning
confidence: 99%
“…"Seeing women as defective in any way is ignorance." (Female,21) "It is a very wrong idea. In the end, not being able to have children is not a lack, but having kids is an extra blessing..." (Male,22) In the focus group discussions, all students concluded that the culture in which they had grown up was the most important factor currently affecting their responses to the idea of an inability to have children.…”
Section: Cultural Influencesmentioning
confidence: 99%
“…19,20 In some traditional societies, the number of children determines a woman's status in society. 21 Turkish society is filled with expressions such as "A home without children is like a chimney that doesn't smoke," implying that a child is an inevitable consequence of marriage. 22 Often, if a couple cannot have children, the woman is accused and placed under social pressure by family elders, acquaintances, or even strangers; this can lead to marital problems, divorce, or, in some parts of Turkey, the taking of a second wife.…”
Section: ö öZ Ze Et T Amentioning
confidence: 99%